Selective exosome exclusion of miR-375 by glioma cells promotes glioma progression by activating the CTGF-EGFR pathway - Xiangdong Xu (Journal of Experimental & Clinical Cancer Research, 2021)
Abstract Background Exosomes are membrane-bound extracellular vesicles of 40–150 nm in size, that are produced by many cell types, and play an important role in the maintenance of cellular homeostasis. Exosome secretion allows for the selective removal of harmful substances from cells. However, it remains unclear whether this process also takes place in glioma cells. Methods Herein, the role of the tumour-suppressor miR-375 was explored in human glioma cells. Immunoblotting and qRT-PCR experiments demonstrated a functional link between miR-375 and its target, connective tissue growth factor (CTGF), which led to the identification of the underlying molecular pathways. The exosomes secreted by glioma cells were extracted by ultracentrifugation and examined by transmission electron microscopy. Exosomal expression of miR-375 was then analysed by qRT-PCR; while the exosome secretion inhibitor, GW4869, was used to examine the biological significance of miR-375 release. Moreover, the dynamics of miR-375 release by glioma cells was investigated using fluorescently labelled exosomes. Finally, exosomal miR-375 release was examined in an orthotopic xenograft model in nude mice. Results MiR-375 expression was downregulated in gliomas. MiR-375 suppressed glioma proliferation, migration, and invasion by inhibiting the CTGF-epidermal growth factor receptor (EGFR) signalling pathway. MiR-375-containing exosomes were also identified in human peripheral blood samples from glioma patients, and their level correlated with disease progression status. Exosomal miR-375 secretion impacted the CTGF-EGFR pathway activity. Once secreted, exosomal miR-375 was not taken back up by glioma cells. Conclusions Exosomal miR-375 secretion allowed for sustained activation of the CTGF-EGFR oncogenic pathway, promoting the proliferation and invasion of glioma cells. These findings enhance our understanding of exosome biology and may inspire development of new glioma therapies.